Enhancing Bamboo Utilization through Experiential Learning and Architectural Applications - Vinsensius Gilrandy Santoso; Dewi Larasati Larasati; Suhendri Suhendri (Arsitektura : Jurnal Ilmiah Arsitektur dan Lingkungan Binaan, 2025)
Bamboo, despite its potential as a sustainable building material, remains underutilized due to limited community perceptions and preferences, shaped by insufficient exposure and understanding. This research addresses the challenge by investigating how individual experiences and learning processes influence community attitudes toward bamboo, aiming to develop strategies to enhance its utilization. A mixed-method approach was employed, collecting data from 259 respondents through open- and closed-ended questionnaires, which were analyzed using regression techniques. The findings reveal that experiential learning plays a crucial role in shaping perceptions. Empirical experiences, such as daily interactions with bamboo-based furniture, significantly increase interest in using bamboo for architectural applications (p < 0.0001). Likewise, passive learning, including reading articles, viewing photographs, or visiting bamboo structures, enhances awareness of its potential as a construction material (p = 0.0002). Additionally, exposure to bamboo in artistic contexts elevates its perceived aesthetic value (p = 0.0004). Given the urgent need to promote sustainable materials, this study emphasizes the transformative impact of experiential learning in shifting community perceptions. By integrating bamboo into daily life—through architectural furniture, artwork, and media exposure—and fostering passive learning initiatives such as exhibitions, educational programs, and awareness campaigns, bamboo’s acceptance and application in the built environment can be significantly expanded. These findings provide a strategic foundation for promoting bamboo as both a functional and aesthetic material, contributing to sustainable construction practices and ecological conservation efforts.